Preliminary Study on a Single Ultrasound-guided Injection of Stromal Vascular Fraction to Treat Partial Rotator Cuff Tears - Sara Di Lorenzo, MD; Andrea Pio Cascino, MD; Antonio Lo Casto, MD; Cesare D’Amico, MD; Bartolo Corradino, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. Partial and complete tears of the rotator cuff tendons are particularly common and debilitating conditions. To date, the standard treatment is conservative, and if symptoms persist, surgical intervention is recommended, preferably using an arthroscopic approach. However, the secondary rupture rate after rotator cuff repair is reported to be as high as 31%, and there is also a significant incidence of stiffness and functional limitation of the affected limb because of the prolonged immobilization. Regenerative therapies may offer alternative solutions. Methods:. In light of these challenges, our study investigated the use of stromal vascular fraction derived from adipose tissue as a regenerative therapy in patients with rotator cuff injuries. We present a case series of 4 patients affected by either acute or chronic partial rotator cuff tendon tears, whom we treated with a single ultrasound-guided injection of autologous stromal vascular factor, obtained by processing adipose tissue harvested from the patient’s abdominal fat. The evolution of tendon regeneration was assessed through clinical examination and radiological imaging, conducted 7 days before the surgery and at 30 and 90 days postinjection. Results:. All patients demonstrated clinical improvement in shoulder function and pain relief. Magnetic resonance imaging confirmed progressive tendon healing in all cases, with no adverse events reported. Conclusions:. Stromal vascular factor–based regenerative therapies represent a solution for tissue repair and regeneration, with further research needed to explore its full potential in orthopedic and other medical applications.